Roll Book Media Roll Book for Early Physical Science - Istiqomah, Nurul; Hapidin; Yetti, Elindra (JPUD - Jurnal Pendidikan Usia Dini, 2021)
Studying physical science and then teaching it to children, as is known from decades of science education research, creates a huge problem of unknown origin. This study aims to develop a media and determine its effectiveness in increasing knowledge of physics for children. This research is a research and development with the stages of the ADDIE model to develop Roll Book media with the roll technique containing physical science material for early childhood. Data collection techniques were carried out through expert validation tests and field trial data. Analysis of effectiveness test data using a paired sample T-test statistical test. The results of the media effectiveness test showed an increase in knowledge of physics in the pre-test and pots-test. The summary of all the test results of the developed media shows that Roll Book products are effectively used to increase children’s knowledge of physics. The concept of storybook media that has been developed in various interesting forms is expected to be an alternative solution for the scientific development of early childhood education studies. Keywords: Early childhood, Physical science, Roll book References: Angelica Torres, & Vitti, D. (2007). A Kinder Science Fair. Science and Children. Arsyad, A. (2013). Media Pembelajaran [Learning Media]. PT Raja Grafindo Persada. Branch, R. M. (2009). Instructional Design: The ADDIE Approach. Springer Science Business Media. California Department of Education. (2012). California Preschool Learning Foundations (Vol. 3). Sacramento. Charlesworth, R., & Lind, K. K. (2012). Math and Science for Young Children. Cengage Learning. https://books.google.co.id/books?id=p5x-3ir8mz4C Citra, A., Hapidin, D., & Akbar, Z. (2019). Pengaruh Model Pembelajaran dan Kemampuan Berpikir Kritis terhadap Pemahaman Sains Fisik. 3(1), 18–29. https://doi.org/10.31004/obsesi.v3i1.136 Dewi, T. H. S., Gunarhadi, & Riyadi. (2018). The Important of Learning Media Based on Illustrated Storybook for Primary School. Proceeding of International Conference on Child-Friendly Education, 233–236. Eshach, H., & Fried, M. N. (2005). Should Science Be Taught in Early Childhood? Journal of Science Education and Technology, 14(3), 315–336. Featherstone, S. (2003). The Little Book of Investigations: Little Books with Big Ideas. Featherstone Education Ltd. Fleer, M. (2015). How Preschools Environments Afford Science Learning. In M. Fleer & N. Pramling (Eds.), A Cultural-Historical Study of Children Learning Science: Foregrounding Affective Imagination in Play-based Settings(pp. 23–37). Springer Netherlands. https://doi.org/10.1007/978-94-017-9370-4_2 Fridberg, M., Jonsson, A., Redfors, A., Thulin, S., Fridberg, M., Jonsson, A., Redfors, A., Thulin, S., Jonsson, A., Redfors, A., & Thulin, S. (2019). Teaching chemistry and physics in preschool: A matter of establishing intersubjectivity establishing intersubjectivity. 0693. https://doi.org/10.1080/09500693.2019.1689585 Gitomer, D. H., & Zisk, R. C. (2015). Knowing What Teachers Know. Review of Research in Education, 39(1), 1–53. https://doi.org/10.3102/0091732X14557001 Greenfield, D. B., Jirout, J., Greenberg, A., Maier, M., & Fuccillo, J. (2009). Early Education and Development Science in the Preschool Classroom: A Programmatic Research Agenda to Improve Science Readiness. October 2014, 37–41. https://doi.org/10.1080/10409280802595441 Gur, C. (2011). Physics in preschool. International Journal of Physical Sciences, 6(4), 939–943. https://doi.org/10.5897/IJPS10.653 Hsiao, C.-Y., & Chang, Y.-M. (2015). A Study of the Use of Picture Books by Preschool Educators in Outlying Islands of Taiwan. International Education Studies, 9(1), 1. https://doi.org/10.5539/ies.v9n1p1 Kalogiannakis, M., Nirgianaki, G. M., & Papadakis, S. (2018). Teaching Magnetism to Preschool Children: The Effectiveness of Picture Story Reading. Early Childhood Education Journal, 46(5), 535–546. https://doi.org/10.1007/s10643-017-0884-4 Kamii, C., & Vries, R. De. (1993). Physical Knowledge in Preschool Education: Implications of Piaget’s Theory. Teachers College Press. Kelemen, D., Emmons, N. A., Seston Schillaci, R., & Ganea, P. A. (2014). Young Children Can Be Taught Basic Natural Selection Using a Picture-Storybook Intervention. Psychological Science, 25(4), 893–902. https://doi.org/10.1177/0956797613516009 Larasati, A., & Yulianti, D. (2014). Pengembangan Bahan Ajar Sains (Fisika) Tema Alam Semesta Terintegrasi Karakter dan berwawasan Konservasi [Development of Teaching Materials for Science (Physics) Themes of the Universe Integrated Character and Conservation insight]. Unnes Physic Education Journal, 3(2), 26–33. Lind, K. K. (2005). Exploring Science in Early Childhood Education. Thomson Delmar Learning. Lorente, L. M. (2017). Implementation of early childhood physical activity curriculum (SPARK) in the Central Valley of California ( USA ). Procedia - Social and Behavioral Sciences, 237(June 2016), 319–325. https://doi.org/10.1016/j.sbspro.2017.02.097 Marton, F. (2014). Necessary conditions of learning. Routledge. Mutmainnah, M., Nessa, R., Bukhari, B., Farhana Mohd Radzif, N., & Kurniawati, R. (2021). Development of Learning Media for Acehnese Culture Picture Books to Get to Know Local Culture in Early Childhood. Al-Athfal: Jurnal Pendidikan Anak, 7(1), 53–72. https://doi.org/10.14421/al-athfal.2021.71-05 Oppliger, P. A., & Davis, A. (2016). Portrayals of Bullying: A Content Analysis of Picture Books for Preschoolers. Early Childhood Education Journal, 44(5), 515–526. https://doi.org/10.1007/s10643-015-0734-1 Oskarsson, M., & Karlsson, K.-G. (1970). Health care or Atom bombs? Interest profiles connected to a science career in Sweden. Nordic Studies in Science Education, 7(2), 190–201. https://doi.org/10.5617/nordina.242 Phillips, E. C., & Sturm, B. W. (2013). Do Picture Books About Starting Kindergarten Portray the Kindergarten Experience in Developmentally Appropriate Ways? Early Childhood Education Journal, 41(6), 465–475. https://doi.org/10.1007/s10643-012-0560-7 Pramitasari, Muktia., Yetti, Elindra., & Hapidin. (2018). Pengembangan Media Sliding Book untuk Pengenalan Sains Kehidupan (Life Science) Kelautan untuk Anak Usia Dini [Development of Sliding Book Media for Introduction to Marine Life Science for Early Childhood]. 12(November), 221–230. https://doi.org/10.21009/JPUD.122.09 Saçkes, M., Akman, B., & Trundle, K. C. (2012). A Science Methods Course for Early Childhood Teachers: A Model for Undergraduate Pre-Service Teacher Education. Necatibey Faculty of Education Electronic Journal of Science and Mathematics Education, 6(2), 1–26. Sari, N. E., & Suryana, D. (2019). Thematic Pop-Up Book as a Learning Media for Early Childhood Language Development. JPUD - Jurnal Pendidikan Usia Dini, 13(1), 43–57. https://doi.org/10.21009/10.21009/jpud.131.04 Sjøberg, S., & Schreiner, C. (2010). The ROSE project—Overview and key findings. March 1–31. Skibbe, L. E., Thompson, J. L., & Plavnick, J. B. (2018). Preschoolers’ Visual Attention during Electronic Storybook Reading as Related to Different Types of Textual Supports. Early Childhood Education Journal, 46(4), 419–426. https://doi.org/10.1007/s10643-017-0876-4 Solfiah, Y. S., Risma, D., Hukmi, & Kurnia, R. (2020). Early Childhood Disaster Management Media Through Picture Story Books. JPUD - Jurnal Pendidikan Usia Dini, 14(1), 141–155. https://doi.org/10.21009/141.10 Thorson, R. M. (2017). Physical Science Teacher’s Guide. Henry David Thoreau In Context.https://doi.org/Https"//Doi.Org/10.1017/9781316569214.025 Thulin, S., & Jonsson, A. (2014). Child Perspectives and Children’ s Perspectives – a Concern for Teachers in Preschool. Educare, 2, 13–37. Thulin, S., & Redfors, A. (2017). Student Preschool Teachers’ Experiences of Science and Its Role in Preschool. Early Childhood Education Journal, 45(4), 509–520. https://doi.org/10.1007/s10643-016-0783-0 Woodard, C., & Davitt, R. (1987). Physical Science in Early Childhood. Thomas Publications.